2018
DOI: 10.1186/s12889-018-6209-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of financial burden, resulting from prescription co-payments, on antihypertensive medication adherence in an older publically insured population

Abstract: IntroductionMedication co-payments represent a financial barrier to antihypertensive medication adherence. The introduction of co-payments for Irish publically insured patients was associated with a 5% reduction in adherence. However there is socioeconomic variability within this population, and the impact may be greater for those on lower income. We evaluated medication-related financial burden of the co-payment in a cohort of Irish publically insured antihypertensive users and tested its association with adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 46 publications
(57 reference statements)
1
21
0
1
Order By: Relevance
“…In our study, we found that elderly, married, and unemployed patients were less likely to receive the treatment. This can be attributed to the huge economic cost the treatment incurs to the patients and their families (16)(17)(18). The total cost associated with MS in Spain was estimated as e1.395 million per year, and e30,050 was the mean annual cost per patient (19).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that elderly, married, and unemployed patients were less likely to receive the treatment. This can be attributed to the huge economic cost the treatment incurs to the patients and their families (16)(17)(18). The total cost associated with MS in Spain was estimated as e1.395 million per year, and e30,050 was the mean annual cost per patient (19).…”
Section: Discussionmentioning
confidence: 99%
“…Education and exercise: Education and exercise were most commonly combined in the review, focused only on physical health, specifically falls [ 20 - 23 ] and physical inactivity [ 24 ]. The interventions were implemented in the same style, consisting of group exercise classes and discussion sessions for participants either before physical activity [ 24 ] or scheduled sporadically with it [ 20 - 23 ]. Participants in these programs reported decreases in mobility limitations [ 24 ] and increases in balance and strength [ 20 - 23 ].…”
Section: Reviewmentioning
confidence: 99%
“…The interventions were implemented in the same style, consisting of group exercise classes and discussion sessions for participants either before physical activity [ 24 ] or scheduled sporadically with it [ 20 - 23 ]. Participants in these programs reported decreases in mobility limitations [ 24 ] and increases in balance and strength [ 20 - 23 ]. Improved self-confidence in one’s abilities [ 20 , 23 ] and social inclusion were cited as additional benefits of participating in these initiatives [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor patient-centered communication may be a derivative of the current payment structure in health care, which limits and disincentivizes the length of time patients have with providers. Cost and financial stress are additional health system barriers to adherence [73][74][75][76]. For example, in a systematic literature review, higher out-of-pocket medical costs were associated with a decrease in medication adherence [77].…”
Section: Health Systemsmentioning
confidence: 99%